Biology and life table of fall armyworm, Spodoptera frugiperda (J.E. Smith) (Lepidoptera: Noctuidae) on maize and rice - Yani Maharani,; Puspitaningrum, Dhita; Noor Istifadah,; Hidayat, Syarif; Ismail, Ade (Pusat Sistematik Serangga, Universiti Kebangsaan Malaysia, 2021)
The fall armyworm, Spodoptera frugiperda (J.E. Smith), is an invasive pest that causes heavy damage to maize in Indonesia and other countries. This is a polyphagous pest attacking more than 300 host plants species, especially on the Poaceae family, such as maize and rice. The biology and life table of S. frugiperda are important for predicting increases in field population and determining the appropriate timing and control techniques. This study was aimed to determine the development period, survival, reproduction, and life table of S. frugiperda on maize and rice. It was conducted in the laboratory under two treatments namely maize-fed larvae and rice-fed larvae, replicated three times, with a total number of 300 individuals observed. The results showed that the type of host plant significantly affected the biology and life table of S. frugiperda. The larvae of S. frugiperda that fed on maize had a larger body size than those fed on rice. The life table of S. frugiperda in both maize and rice was 32.24 and 37.90 days, respectively. Meanwhile, the female longevity at 25.7oC from the egg until imagos death on maize and rice was 44.55 and 50.25 days, and 43.79 and 48.61 days for males, respectively. The fecundity was higher for maize-fed larvae at 261.88 eggs per female compared to rice-fed at 172.36 eggs per female. The intrinsic rate (rm) was significantly different between the two hosts, with a higher rate of 0.209 individual per parent per day on maize-fed compared to the rice-fed larvae at 0.154 individual per parent per day. The maximum values of rm alongside the net reproductive rate (Ro), the finite rate of increase (λ), the shortest mean generation time (T), and doubling time (DT) was also calculated, which indicated that maize was more favorable for the life of S. frugiperda. These findings are useful for predicting the development of S. frugiperda populations on both host plants and that they can be used as references to determine appropriate control.